Formative research, direct link to scientific research - Ferreyros Morón, Juan (2021)
An investigation, -as a general concept, means: to deepen some topic or "idea", and therefore, said "idea" has awakened deep curiosity, which has impacted the reader in such a way that he feels obliged to scrutinize more bottom; to search, experiment, interact with other people, organizations; among others, that is, it is proven that this is how an investigation is born.